A Miniaturized Flexible Surface Electromyography Sensor With an Integrated Localization Concept - Balbach, Samira; Kolpak, Jasmin; Dorn, Christian; Brückner, Stefan; Schlechtweg, Niklas; Gambietz, Markus; Koelewijn, Anne; Vossiek, Martin; Hagelauer, Amelie (IEEE Microwave Magazine, 2025)
Recent developments in sensor technology have allowed researchers to investigate the potential of using human movement measurements for unobtrusive diagnosis and monitoring of prevalent neuromuscular disorders such as Parkinson’s disease (PD) or joint osteoarthritis. Disease diagnosis and monitoring require both information about the movement itself (kinematics) and the muscle forces that drive it (kinetics). Although the movement reflects the impairment, the forces reveal its underlying cause [1]. The millimeter-level tracking accuracy achieved in our previous work within the Collaborative Research Center (CRC) “Empathokinaesthetic Sensor Technology—Sensor Techniques and Data Analysis Methods for Empathokinaesthetic Modeling and Condition monitoring” (CRC 1483 “EmpkinS”) [2] enables the detection of small movement differences. Additionally, recent advances in optimal control [3], [4], [5] and machine learning [6] have enabled the accurate estimation of kinematic and kinetic movement parameters outside of laboratory environments and across various sensor types. These optimal control problems are solved by minimizing an objective related to energy minimization, which replicates the central nervous system’s approach to movement planning [7]. However, this method has been shown to inaccurately predict muscle activity [8]. This inaccuracy is thought to arise from the failure to account for uncertainty and randomness as it is known that optimal muscle contraction differs in environments with randomness compared to those without [9]. Furthermore, the energy optimality of movement might not be a valid assumption in patients with neuromuscular disease, for example, in PD [10
Keywords: Location awareness; Radio frequency; Electrodes; Neuromuscular; Optimal control; Kinematics; Sensor systems; Kinetic theory; Microwave filters; Monitoring

A Wireless Joint Communication and Localization EMG-Sensing Concept for Movement Disorder Assessment - Brückner, Stefan; Weber, Jasmin; Michler, Fabian; Shanin, Nikita; Schober, Robert; Hagelauer, Amelie; Weigel, Robert; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Vossiek, Martin (IEEE Journal of Electromagnetics, RF and Microwaves in Medicine and Biology, 2023)
Real-time sensory recording of the musculoskeletal system function is an important tool for the diagnosis, treatment planning, and optimal treatment execution of diseases, such as Parkinson's disease and osteoarthritis. This article presents a new wireless joint communication and localization electromyography (EMG)-sensing concept. An on-body sensor beacon measures EMG signals and wirelessly transmits them. At the same time, the spatial position and movement of the beacon is determined with high precision in real time using these transmitted radio signals. The seamless integration of multiple sensors avoids the need to synchronize and individually set up multiple independently operating sensors. An outstanding feature of the radio localization approach is that it does not require proprietary ultra-wideband signals or complicated time synchronization protocols, allowing for small and energy-efficient implementation. To demonstrate this novel concept, a wireless 3D-localizable EMG sensor was developed and experimentally evaluated. This new type of sensing concept allows, for the first time, the time-synchronous measurement of muscle activity and the underlying movement of the associated body part. URL: https://ieeexplore.ieee.org/stamp/stamp.jsp?tp=&arnumber=10286030&isnumber=8000303<br
Keywords: Array signal processing; EMG; localization; radar tracking; radio communication

Characterization of a Flexible Polymer-Based Substrate Material for RF Applications - Michler, Fabian; Kolpak, Jasmin; Scheiner, Benedict; Weigel, Robert; Hagelauer, Amelie (IEEE Radio and Wireless Symposium (RWS), 2023)

Remote powered medical implants for Telemonitoring (Invited Paper) - Walk, Jasmin; Kolpak, Jasmin; Söll, Christopher; Weigel, Robert; Fischer, Georg; Ußmüller, Thomas (Proceedings of the IEEE, 2014)
Chronicle diseases like diabetes mellitus often need a permanent monitoring of vital signs. Especially the use of telemedicine might increase the quality of life for concerned patients. New systems are required which permanently detect and provide health status information. But, these systems must not control patient’s life and shall work autonomous. For this purpose, intelligent medical implants are well qualiﬁed. The present work describes a system for wireless power supply and communication with medical implant applications. Monitoring vital signs might lead to a big amount of data. Therefore, high data rates are necessary provided by high operating frequencies. High frequencies in turn lead to high attenuation losses because of the frequency dependent relative permittivity ε_r of the human body. Hence, high frequencies are not suitable for energy transfer through the human body. The presented concept is based on two different frequencies for power supply and data transmission. An independent devel- opment of both blocks is possible. The power supply operates on 13.56 MHz using inductive coupling. Thereby, the human body doesn’t affect the energy transfer. In contrast, the data transmission is operated by a frequency of the Medical Implant Communication Service band. The elaborated system consists of an power supply unit, a data transmission unit and a control unit. The implementation of the power supply and data transmission as well as associated theoretical basics are presented. Performed measurements demonstrate that the realized system is qualiﬁed for the use on human beings.
elib2cris::1512001600,walk2014
Keywords: biological tissues; biomedical communication; biomedical power supplies; energy storage; frequency domain analysis; implantable biomedical devices; permittivity